Media Pengembangan Soft Skills Siswa dalam Pembelajaran PAI - Iskandarsyah Iskandarsyah; Abdul Fattah Nasution (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The emphasis on critical thinking in Islamic religious education is categorized as low, in fact currently teachers also emphasize hard skills more than soft skills. This situation is caused by the tradition of Islamic religious education which tends to be pessimistic and demands total obedience which influences the thinking style of students to be submissive. without asking too many questions. This research aims to determine the media that can be used to develop students' soft skills in PAI learning, namely creative critical thinking (CCT), interpersonal and intrapersonal. The use of qualitative research with literature study was chosen in this paper in order to obtain supporting information related to the problems presented. Data analysis was carried out by looking at the need for soft skills in PAI learning based on previous research and then linking it to various media that can be used to develop students' soft skills in PAI learning. Based on this, it was found that the media that can be used are media in which there is the use of technology in the form of audiovisual, the use of media based on the introduction of material, as well as the role of teachers and parents as visual media.